2010
DOI: 10.1111/j.1460-9592.2010.03389.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental pharmacology of tramadol during infancy: ontogeny, pharmacogenetics and elimination clearance

Abstract: The phenotypic observations might in part explain unanticipated (side-)effects of tramadol. In addition to the compound-specific clinical implications, it is important to stress that the maturational trends in the elimination processes described can be considered for other compounds (e.g., codeine) that undergo similar elimination routes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 40 publications
3
56
0
Order By: Relevance
“…Studies conducted in the past two decades show major deficiencies with pediatric dosing methods built on allometry [48]. Optimal drug safety and efficacy in this vulnerable population requires an increased understanding of the impacts of physiological maturation and genetic variation on drug-metabolizing enzymes [911]. One such enzyme, CYP2D6, participates in the elimination of approximately 15% of clinically used drugs metabolized by cytochrome P450s [12], including antipsychotics and antidepressants, beta-blockers, opioid analgesics [13,14] and the antitussive dextromethorphan (DM) [15].…”
mentioning
confidence: 99%
“…Studies conducted in the past two decades show major deficiencies with pediatric dosing methods built on allometry [48]. Optimal drug safety and efficacy in this vulnerable population requires an increased understanding of the impacts of physiological maturation and genetic variation on drug-metabolizing enzymes [911]. One such enzyme, CYP2D6, participates in the elimination of approximately 15% of clinically used drugs metabolized by cytochrome P450s [12], including antipsychotics and antidepressants, beta-blockers, opioid analgesics [13,14] and the antitussive dextromethorphan (DM) [15].…”
mentioning
confidence: 99%
“…In newborn infants, Mikhel'son et al 21 used tramadol for postoperative analgesia in 20 patients and reported adequate pain control. The analgesic efficacy of tramadol is partly dependent on its CYP2D6 -induced- O -desmethyl metabolite that exhibits an age-dependent maturation pattern 22. Therefore, CYP2D6 polymorphisms could possibly interfere in the pharmacological action of tramadol on studied infants, and at least 19 different alleles and 5 allele duplications have been already identified in African and European Brazilians 23.…”
Section: Discussionmentioning
confidence: 99%
“…Age CYP2D6 seems to be functional already in first 2 weeks after birth [85][86][87] and seems generally not to decline substantially with older age; however, definite information is relatively sparse [88,89]. The article by Doki et al [89] found an interesting dependence of the age-related decline in flecainide clearance from the CYP2D6 genotype.…”
Section: Pregnancymentioning
confidence: 93%